Pathogenomics of Virulence Traits of Plesiomonas shigelloides That Were Deemed Inconclusive by Traditional Experimental Approaches - Ekundayo, Temitope C.; Okoh, Anthony I. (Frontiers in Microbiology, 2018)
One of the major challenges of modern medicine includes the failure of conventional protocols to characterize the pathogenicity of emerging pathogens. This is particularly apparent in the case of Plesiomonas shigelloides. Although a number of infections have been linked to this microorganism, experimental evidence of its virulence factors (VFs), obtained by traditional approaches, is somewhat inconclusive. Hence, it remains unclear whether P. shigelloides is a true or opportunistic one. In the current study, four publicly available whole-genome sequences of P. shigelloides (GN7, NCTC10360, 302-73, and LS1) were profiled using bioinformatics platforms to determine the putative candidate VFs to characterize the bacterial pathogenicity. Overall, 134 unique open reading frames (ORFs) were identified that were homologous or orthologous to virulence genes identified in other pathogens. Of these, 52.24% (70/134) were jointly shared by the strains. The numbers of strain-specific virulence traits were 4 in LS1; 7 in NCTC10360; 10 in 302-73; and 15 in GN7. The pathogenicity islands (PAIs) common to all the strains accounted for 24.07% ORFs. The numbers of PAIs exclusive to each strain were 8 in 302-73; 11 in NCTC10360; 14 in GN7; and 18 in LS1. A PAI encoding Vibrio cholerae ToxR-activated gene d protein was specific to 302-73, GN7, and NCTC10360 strains. Out of 33 antibiotic multi-resistance genes identified, 16 (48.48%) genes were intrinsic to all strains. Further, 17 (22.08%) of 77 antibiotic resistance islands were found in all the strains. Out of 23 identified distinct insertion sequences, 13 were only harbored by strain LS1. The number of intact prophages identified in the strains was 1 in GN7; 2 in 302-73; and 2 in NCTC10360. Further, 1 CRISPR element was identified in LS1; 2 in NCTC10360; and 8 in 302-73. Fifteen (78.95%) of 19 secretion systems and secretion effector variants were identified in all the strains. In conclusion, certain P. shigelloides strains might possess VFs associated with gastroenteritis and extraintestinal infections. However, the role of host factors in the onset of infections should not be undermined.